2014
DOI: 10.28945/2023
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and Innovation - Reframing Innovation Activities for a Matrix Organization

Abstract: In this article we point out the importance of reframing and orchestrating an innovation process while adopting a matrix organization (MO) structure. Some studies implicate that a MO gives the flexibility desired and supports sharing of information and efficient use of resources in an organization. However, the MO is also a target of hard criticism by real life operational actors in organizations performing daily tasks. To find out reasons behind this gap, we studied the transformation phase of an organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
5
0
1
Order By: Relevance
“…Without support and activity from the employees, no structure can make innovation potential as an asset to the firm. Mäkimattila et al (2012) have suggested that instead of having a matrix as the final solution, firms should think how they can make it possible to form temporal teams collaboratively intraand inter-organizationally to carry out innovation tasks. Although turning into the matrix structure has helped to create unitary innovation capability at least to some extent, especially the innovation structures seem still to be a development target for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Without support and activity from the employees, no structure can make innovation potential as an asset to the firm. Mäkimattila et al (2012) have suggested that instead of having a matrix as the final solution, firms should think how they can make it possible to form temporal teams collaboratively intraand inter-organizationally to carry out innovation tasks. Although turning into the matrix structure has helped to create unitary innovation capability at least to some extent, especially the innovation structures seem still to be a development target for the future.…”
Section: Discussionmentioning
confidence: 99%
“…Intellectual Commons [57] Knowledge Management in Libraries in the 21st Century Knowledge Commons [71] The unacknowledged parentage of knowledge management Knowledge Commons-Cities [62] Knowledge repositories in knowledge cities: institutions, conventions and knowledge subnetworks Knowledge Commons-Cities [61] Knowledge cities through "open design studio" educational projects: the case study of Jeddah City Commons-Generic [72] Understanding computer-mediated inter-organizational collaboration: a model and framework Commons-Generic [65] Knowledge clusters and knowledge hubs: designing epistemic landscapes for development Commons-Generic [73] Interaction and innovation-reframing innovation activities for a matrix organization…”
Section: Peripheral: Innovation-centric Knowledge Commons (N = 22)mentioning
confidence: 99%
“…Os demais temas foram o big data em 5 artigos (Comuzzi & Patel, 2016;Erevelles, Fukawa, & Swayne, 2015;Gupta & George, 2016;Wamba, et al, 2017;Braganza, Brooks, Nepelski, Ali, & Moro, 2017), o comércio eletrônico em 5 artigos (Erevelles, Fukawa, & Swayne, 2015;Hua, Morosan, & Franco, 2015;Groesser & Jovy, 2016;Tan, Guo, Cahalane, & Cheng, 2016;Braganza, Brooks, Nepelski, Ali, & Moro, 2017) Quanto a dimensão teórica utilizada junto às Capacidades Dinâmicas (CD), as teorias mais adotadas nos artigos são o desempenho com 11 artigos (Gupta & George, 2016;Wamba, et al, 2017;Hua, Morosan, & Franco, 2015;Marolt, Pucihar, & Zimmermann, 2015; Análise estrutural e longitudinal sobre capacidades dinâmicas em agências de publicidade e em mídias sociais Kim, 2017;Ahani, Rahim, & Nilashi, 2017;Wilden & Gudergan, 2015;Morgan, 2012;Yun & Gloor, 2015;Palacios-Marqués, Merigo, & Soto-Acosta, 2015;Kamboj & Rahman, 2015), o marketing com 8 artigos (Wang, Lai, & Chang, 2016;Wilden & Gudergan, 2015;Kamboj & Rahman, 2015;Zavattaro & Daspit, 2016;Josephson, Johnson, & Mariadoss, 2016), (Kumar, Dixit, Javalgi, & Dass, 2016), a inovação com 7 artigos (Kamprath & Mietzner, 2015;Zavattaro & Daspit, 2016;Mäkimattila, Saunila, & Salminen, 2014;Dong & Wu, 2015;Yoo, Henfridsson, & Lyytinen, 2010;…”
Section: Análise Dos Temas Abordadosunclassified